The Influence of Motivation, Discipline and Work Environment on the Performance of Afdeling 1 PTPN IV Regional III Kebun Sei Galuh Employees. - Ferisca Nurwidyanti; Faisal Yudha (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The aim of this research is to determine the influence of Motivation, Discipline and Work Environment on employee performance at PTPN IV Regional III Kebun Sei Galuh. The sample in this study was 45 employees of Afdeling 1 PTPN IV Regional III Kebun Sei Galuh. Based on the research results, the correlation value (R) is 0.934. This figure shows that there is a strong link between the independent variable and the dependent variable at PTPN IV Regional III. Meanwhile, the R Square value is 0.872, which shows that Motivation, Work Discipline and Work Environment as a whole have an effect of 87.2% on the performance of PTPN IV Regional III employees. Partially motivation with a significance value of 0.013 is smaller than alpha 0.05. So motivation has a significant effect on the performance of Afdeling I PTPN IV Regional III Kebun Sei Galuh employees. Work Discipline with a significance value of 0.038 is smaller than alpha 0.05. Simultaneously, with a significance of 0.000 which is smaller than alpha 0.05, it means that the variables Motivation, Work Discipline and Work Environment simultaneously have a significant effect on the performance of Afdeling I PTPN IV Regional III Kebun Sei Galuh employees. The multiple linear regression equation is as follows: Y = 0,984 + 0,299X1 + 0,241X2 + 0,402X3 + ε